2011
DOI: 10.2298/tsci100601002b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of operating conditions on the performance of the bubble pump of absorption-diffusion refrigeration cycles

Abstract: The mathematical model will be able to predict the operated condition (required tube diameters, heat input and submergence ratio….). That will result in a successful bubble pump design and hence a refrigeration unit. In the present work a one-dimensional two-fluid model of boiling mixing ammonia-water under constant heat flux is developed. The present model is used to predict the outlet liquid and vapor velocities and pumping ratio for different heat flux input to pump. The influence of operated conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The velocity slip with the heat flux, 2.83 kW/m 2 using water as the working fluid is 0.3 m/s [14] and in the current study, the corresponding value is 0.317m/s. The void fraction at 20 kW/m 2 in the study using ammonia/water [13] is 0.98 and in the present study is 0.94. The variation is only 4-6% with the present model and hence the validation is acceptable.…”
Section: Model Validationsupporting
confidence: 47%
See 2 more Smart Citations
“…The velocity slip with the heat flux, 2.83 kW/m 2 using water as the working fluid is 0.3 m/s [14] and in the current study, the corresponding value is 0.317m/s. The void fraction at 20 kW/m 2 in the study using ammonia/water [13] is 0.98 and in the present study is 0.94. The variation is only 4-6% with the present model and hence the validation is acceptable.…”
Section: Model Validationsupporting
confidence: 47%
“…Increasing heat flux for a fixed time or increasing the time of heating leads to increase the amount of heat received by the mixing flow. By refereeing to void fraction values, flow patterns are defined as a bubbly flow for a void fraction less than 0.3, slug flow for void fraction between 0.3 and 0.55, churn flow for void fraction between 0.55 and 0.8 and annular flow for a void fraction more than 0.8 [13]. By examining the different contours at the different time and different heat flux, we can realise the important results.…”
Section: Void Fraction Contoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, solar energy is the most promising unconventional energy sources. Solar energy has many factors in its favor with respect to availability, green environment and renewability [2][3][4]. This work involves operate refrigeration system with the use of solar energy.…”
Section: Introductionmentioning
confidence: 99%
“…Benhmidene et al (2011a) investigated the optimization of the heat flux density received by a bubble pump and correlated the minimum heat flux density for pumping a water-ammonia solution as a function of the tube diameter of the bubble pump and mass flow rate of the two-phase flow. In addition, Benhmidene et al (2011b) studied the influence of the operating conditions such as the tube diameter, pressure, and ammonia mass fraction in the solution at the bubble pump entrance on the flow parameters at the bubble pump exit. The authors concluded that tube diameter is the parameter that influences the bubble pump operation the most.…”
Section: Introductionmentioning
confidence: 99%